The Personality Oriented Concept of Students’ Musical Thinking Development in Higher Educational Institutions of Art - Pikhtar, Olena (Vìsnik Kiïvsʹkogo nacìonalʹnogo unìversitetu kulʹturi ì mistectv. Serìâ: Muzične mistectvo, 2019)
The personality oriented concept of students’ musical thinking development in higher educational institutions of art is analyzed in the article. Planning of educational process with the regularities of development and the individual self-development creates the favorable conditions for self-realization of the creative potential of future musicians-performers and for activation of their musical thinking. The peculiarity of the students’ musical thinking development in the context of the personality oriented approach, as an important factor of the process of professional training improvement, is revealed. The purpose of the article is to substantiate the personality oriented concept of harmonious development of students’ musical thinking in art higher educational institutions, the expediency of implementation in the process of professional training of future musicians-performers of a personality oriented methodical system of education. The basic ways of development of students’ musical thinking were defined. They are appliance in the educational process of the humanistic model of professional training of future musiciansperformers, which provides the personality oriented methods of teaching; researching of the musical thinking of students from the positions the interconnection of intellectual, emotional and personal development; the usage of personality oriented situations, in the process of which the creative musical and cognitive activity of students activates, the introduction of dialogue as a mean of subject-subjective relations formation in the musical lessons. It is proved that the effectiveness of the musical thinking development is in the direct correlation dependency from the personal qualities and characteristics of students’ musical thinking development. The most perspective forms and methods of personality oriented learning in the development of students’ musical thinking, which motivate to think independently, direct the musical thinking of students to active productive actions, creative artistic and interpretive activity, and creativity, are investigated. A complex of methods, which are directed on the activation of musical thinking in the process of personality oriented education, are applied, namely: solution of thoughtful musical tasks, personality oriented training, stylistic interpretation, analytical cognition of a musical composition, instrumental dialogue, improvisation, etc. Scientific novelty consists in the scientific and methodical development of the personality oriented concept of professional training of future musicians-performers as a whole structural process, It is directed on the the musical thinking development of students on a base of a personality oriented approach. Conclusions. The expediency of the personality oriented concept of the musical thinking development of students made it possible to develop a methodical system of phased formation of musical thinking, which will provide the effective professional training of the future musiciansperformers in the art higher educational institutions.